Becoming a Wild Researcher Through Goethean Science, Indigenous Philosophy and Creative Response - Lee Beavington (Australian Journal of Environmental Education)
Framed by biological and environmental education, this paper addresses eight questions posed in Wild Pedagogies: Touchstones for Re-Negotiating Education and the Environment in the Anthropocene. These questions ponder more-than-human methodologies, positionality of the natural world, embedded anthropocentricism and research implications for the natural world. Wild pedagogues aim to reclaim and reimagine an educational system toward intentional praxis less reliant on quantifiable learning outcomes, with a move toward active, ‘‘self-willed pedagogy’’ with an agential nature as co-teacher. This bold enterprise challenges dominant Western-colonial paradigms rooted in power and control over nature and learners. My responses explore Tim Ingold’s notion of a ‘‘modest, humble, and attentive’’ science, ecocentric place-based research, questions dissection and animal experimentation, and offers Goethean science and Indigenous philosophy as alternatives to rational-reductionist Newtonian science. Lab-based science is contrasted with natural history, and creative, contemplative practice are suggested as tools of the wild researcher. How can we transform science education through the lenses of deep ecology and philosophical posthumanism? This paper contributes to the ongoing dialogue of ecological and environmental education during the Anthropocene, especially in regard to the life sciences and the often-unquestioned use of nonhuman animals in science teaching and research.